Impact of the Petrivsko-Kreminsky deep fault on the fluid migration in rocks of the Svyatohirsk brachyanticline - Pyvovarov, Anton (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Introduction. Deep regional faults serves as primary pathways for fluid mass migration in the Dnipro-Donetsk aulacogen, particularly affecting fold faults and anticline structures. The interaction between heated fluid migration and structural development is evident in the Svyatohirsk brachyanticline structure and the Petrivsko-Kreminsky deep fault, where numerous geochemical and thermohydrodynamic inversions demonstrate their systematic influence on adjacent structures.Problem definition. This study examines how the Petrivsko-Kreminsky deep fault and its secondary fractures impact hydrogeochemical and thermohydrogeodynamic processes in the Svyatohirsko-Kamyanska deposit area. The periodic tectonic activation of crustal-mantle centers intensifies heat and mass transfer in fluid flows, particularly in unloading zones along deep faults, where rapid and impulsive migration of heated fluid masses occurs, transporting rock particles and charged ions from underlying strata and the basement.Purpose of the article. The research aims to analyze the impact of the Petrivsko-Kreminsky regional deep fault on the Svyatohirsk brachyanticline structure and its associated geological processes, focusing on the mechanisms of fluid migration and their influence on rock formations.Analysis of recent research. Previous studies have documented significant thermohydrodynamic anomalies in Upper Cretaceous sediments, with temperatures ranging from 23°C to 27°C compared to background temperatures of 10°C to 12°C.Tectonical configuration. The Svyatohirsk brachyanticline, formed during the Palatinate phase of Hercynian tectogenesis, contains numerous discontinuous faults attached to the Petrivsko-Kreminsky deep fault. Modern tectonic movements are reflected in varying uplift rates: 1.4-2.9 mm/year for the hanging wing and 5.2-11.1 mm/year for the lying wing, creating visible relief differences.Deep fault impact on fluid migration. These fault structures facilitate vertical fluid and heat flow migration from deeper crustal and mantle layers. This results in localization of hydrogeochemical inversions, evidenced by groundwater enrichment with endogenous elements (helium, radon, argon, CO2). The isotopic composition (δ13C: 5-8‰) indicates thermometamorphic origin and deep degassing processes from the mantle. The activity of deep faults has impacted the lithological composition, increasing reservoir rock density through pyritization, ferruginousness, secondary quartz, and carbonation processes.Geological model and practical significance. Deep-seated fractures act as conduits for heated fluid migration, disrupting natural thermal gradients and causing thermohydrogeodynamic inversions. These processes contribute to secondary mineralization and cementation of fracture networks within reservoir rocks, significantly influencing the region's lithological characteristics. The model reveals that during both current and future tectonic activations, this process will continue intermittently, though with progressively less impact on the cement substance, while leading to accumulation of endogenous gas. The correlation between inversions and tectonic structures offers significant potential for identifying geological features and predicting hydrocarbon accumulations, particularly in areas where deep fault zones intersect with anticline structures.